2020
DOI: 10.1104/pp.20.00024
|View full text |Cite
|
Sign up to set email alerts
|

PHYTOCHROME-INTERACTING FACTOR-LIKE14 and SLENDER RICE1 Interaction Controls Seedling Growth under Salt Stress

Abstract: Early seedling development and emergence from the soil, which are critical for plant growth and important for crop production, are controlled by internal factors, such as phytohormones, and external factors, such as light and salt. However, little is known about how light and salt signals are integrated with endogenous cues in controlling plant physiological processes. Here, we show that overexpression of rice (Oryza sativa) PHYTOCHROME-INTERACTING FACTOR-LIKE14 (OsPIL14) or loss of function of the DELLA prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(50 citation statements)
references
References 48 publications
2
34
0
Order By: Relevance
“…For example, among six OsPILs (OsPIL11 to OsPIL16) ( Nakamura et al, 2007 ), the T-DNA insertion knockdown rice of OsPIL13 exhibited a pale-green phenotype with the downregulation of several genes involved in chlorophyll biosynthesis ( Sakuraba et al, 2017 ), and the CRISPR/Cas9-mediated knockout rice of OsPIL15 increased the number of cells in the grains ( Ji et al, 2019 ). Furthermore, rice and maize plants overexpressing PIFs exhibited phenotypes related to seedling growth, internode elongation, and chlorophyll biosynthesis ( Todaka et al, 2012 ; Zhou et al, 2014 ; Sakuraba et al, 2017 ; Shi et al, 2017 ; Mo et al, 2020 ). Here, we also reported similar phenotypes, but along with the positive regulatory roles of BdPIL1 and BdPIL3 in floral induction, which might be correlated with the expression of both BdPIL1 and BdPIL3 in the flower tissues ( Figure 1E ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, among six OsPILs (OsPIL11 to OsPIL16) ( Nakamura et al, 2007 ), the T-DNA insertion knockdown rice of OsPIL13 exhibited a pale-green phenotype with the downregulation of several genes involved in chlorophyll biosynthesis ( Sakuraba et al, 2017 ), and the CRISPR/Cas9-mediated knockout rice of OsPIL15 increased the number of cells in the grains ( Ji et al, 2019 ). Furthermore, rice and maize plants overexpressing PIFs exhibited phenotypes related to seedling growth, internode elongation, and chlorophyll biosynthesis ( Todaka et al, 2012 ; Zhou et al, 2014 ; Sakuraba et al, 2017 ; Shi et al, 2017 ; Mo et al, 2020 ). Here, we also reported similar phenotypes, but along with the positive regulatory roles of BdPIL1 and BdPIL3 in floral induction, which might be correlated with the expression of both BdPIL1 and BdPIL3 in the flower tissues ( Figure 1E ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the plants of both RNAi lines exhibit increased expression of BdSAUR and BdGA20ox2 genes ( Figures 5E,F ), which might correlate with the tall phenotype, because these genes play roles in promoting elongated growth ( Rieu et al, 2008 ; Stortenbeker and Bemer, 2019 ). Previously, OsPIL13 and OsPIL14 have been shown to bind to the promoters of the genes, such as OsPORB ( Sakuraba et al, 2017 ; Mo et al, 2020 ). Thus, we analyzed the DNA-binding ability of BdPIL1 and BdPIL3 with the promoter sequences of selected target genes, namely, BdPOR , BdMIR156H , and BdSAUR50 , and suggested that BdPIL1 and BdPIL3 regulated the transcription of target genes by directly binding to the corresponding promoters ( Figure 7 and Supplementary Figures 12 , 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…The expression of OsAGO18 can be activated by jasmonate (JA) signalling [ 40 ]. OsSLRL1 is a DELLA family protein that regulates plant hormone metabolism and mediates the growth and development of plants [ 41 – 43 ]. qRT-PCR was performed and the relative expression levels of the selected candidate genes were determined in plants infected by the virus from 0 to 16 days.…”
Section: Resultsmentioning
confidence: 99%
“…Salinity is another major abiotic stress that is globally distributed in both irrigated and non-irrigated areas [16,17]. On a global basis, salinity stress ranked second after the drought [18].…”
Section: Introductionmentioning
confidence: 99%
“…As NUE for rice plants under salt-affected soils is relatively lower than those on normal soils, the judicious use of nitrogenous fertilizer application in saline soil is needed. Breeders involved in salinity tolerant rice, it is groundbreaking news that the overexpression of PHYTOCHROME-INTERACTING FACTOR-LIKE14 (OsPIL14), or loss of function of the DELLA protein SLENDER RICE1 (SLR1), accelerate mesocotyl and root growth under salt stress and minimize the sensitivity to NaCl-induced hindrance of seedling growth in rice [17].…”
Section: Introductionmentioning
confidence: 99%